St. Louis Paper - The Coal Industry of Illinois (with Discussion) - C. M. Young (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The following paper has been prepared with the object of placing on record in the Transactions some facts concerning the present condition and future prospects of the coal industry of Illinois. In presenting it, the writer wishes to say that a considerable amount of the material contained is taken from the publications and records of the Illinois Coal Mining Investigations, the annual Coal Report of the State Mining Board, and the work of the State Geological Survey. Coal Beds and Mining Methods According to the latest maps of the State Geological Survey, there are only 19 of the 102 counties of the State some portion of whose territory is not within the borders of the coal measures. If outlying areas in Calhoun and Whiteside Counties are considered, the number is reduced to 17. This does not mean that all of the 85 counties that are partly or wholly underlain by coal measures will become producers, as there are some portions of the State in which the coal does not occur in beds of such thickness as to warrant the hope that it can be mined. The mining of coal is widespread, however, for in 1916 there was production from 61 of the 102 counties of the State, There seem to be no cases in which operations will be limited by depth, as none of the coal measures lie at depths much greater than those at which it has been proved that coal may be profitably mined in this field. In fact, the deepest shaft reaching a bed of bituminous coal in the United States is located in this State at Assumption, where coal only 3 ½ ft. (1.07 m.) thick is worked at a depth of 1004 ft. (306 m.). The coal beds occur in the form of a basin which is deepest along a line extending through the central part of the State and bearing a little west of north. The northern, western and southern borders of this basin lie within the boundaries of the State, but on the eastern side the Illinois field is continuous with the Indiana field. The glacial drift covers all except the extreme southern end of the State and the visible outcropping